Pengaruh Literasi Keuangan dan Gaya Hidup Hedonisme Terhadap Pengelolaan Keuangan Mahasiswa yang Kos di Surakarta - Ratih Rahmaningrum; Imronudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Globalization has changed many behaviors, especially economic behavior. Supported by students' consumerist attitudes and advances in technology, it makes it easier for them to spend their money. Generation Z also likes branded products at expensive prices. This causes their expenses to be high. Therefore, it is important for Generation Z to master financial understanding in order to manage their finances optimally, so they can be smarter in using money. This research aims to analyze the influence of financial literacy and a hedonistic lifestyle on the financial management of boarding house students in Surakarta, with a sample of 176 people who are students at the Muhammadiyah University of Surakarta. Data was collected using a questionnaire and analyzed using SmartPLS. The results of this research prove that financial literacy and a hedonistic lifestyle have a positive and significant effect on financial management.